Association of Evaluated Glomerular Filtration Rate and Incident Diabetes Mellitus: A Secondary Retrospective Analysis Based on a Chinese Cohort Study - Mo, Zihe; Hu, Haofei; Du, Xiaoqing; Huang, Qingli; Chen, Ping; Lai, Linjing; Yu, Zhiqun (Frontiers in Medicine, 2022)
Background: Previous studies have revealed that chronic kidney disease (CKD) is a significant risk factor for insulin resistance and diabetes. However, few studies are on the association between estimated glomerular filtration rate (eGFR) and incident diabetes, especially in the Chinese population with eGFR>60 mL/min·1.73 m2. This study explored the relationship between eGFR and incident diabetes in a large cohort in the Chinese community. Methods: The present study was a retrospective cohort study. A total of 199,435 adults from Rich Healthcare Group in China were studied, including all medical records for participants who received a health check from 2010 to 2016. The target-independent and dependent variables were eGFR measured at baseline, and incident diabetes mellitus appeared during follow-up. After testing the proportion hypothesis, Cox proportional-hazards regression was used to investigate the association between eGFR and incident diabetes. A Cox proportional hazards regression with cubic spline functions and smooth curve fitting (the cubic spline smoothing) was used to identify non-linear relationships between eGFR and the risk of diabetes. Additionally, we also performed subgroup analysis and a series sensitivity analysis. It was stated that the data had been uploaded to the DATADRYAD website. Result: After adjusting gender, body mass index, systolic blood pressure, diastolic blood pressure, fasting plasma glucose, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, alanine aminotransferase, aspartate aminotransferase, smoking and drinking status and family history of diabetes, the result showed eGFR was negatively associated with incident diabetes (HR=0.986, 95%CI (0.984, 0.988)). A non-linear relationship was detected between eGFR and incident diabetes, with an inflection point of eGFR of 98.034 mL/min·1.73 m2. The effect sizes and the confidence intervals on the left and right sides of the inflection point were 0.998 (0.993,1.003) and 0.976 (0.972,0.980), respectively. Subgroup analysis showed a stronger association in women, never smokers, the population with FPG<6.1mmol/L, BMI<24kg/m2, SBP<140mmHg, DBP<90mmHg and family history without diabetes. Conclusion: eGFR is independently associated with incident diabetes. The relationship between eGFR and incident diabetes is also non-linear. eGFR is strongly related to incident diabetes when eGFR was above 98.034 mL/min·1.73 m2.